Recent Advances in Noble Metal Nanoparticles for Cancer Nanotheranostics - Dhiraj Kumar; Isha Mutreja; Ajeet Kaushik (Journal of Nanotheranostics, 2023)
The limitations of current treatment strategies for cancer management have prompted a significant shift in the research and development of new effective strategies exhibiting higher efficacy and acceptable side effects. In this direction, nanotheranostics has gained significant interest in recent years, combining the diagnostic and therapeutic capabilities of nanostructures for efficient disease diagnosis, treatment, and management. Such nano-assisted platforms permit the site-specific release of bioactive cargo in a controlled fashion while permitting non-invasive real-time in situ monitoring. A plethora of materials has been developed as pharmacologically relevant nanoformulations for theranostic applications ranging from metallic to lipid and polymer-based composite systems, with each offering potential opportunities and its own limitations. To improve advancements with better clarity, the main focus of this review is to highlight the recent developments focusing on using different noble metal nanoparticles (noble MNPs) as cancer nanotheranostic agents, highlighting their properties, advantages, and potential modifications for their successful utilization in personalized medicine. The advantage of using noble metals (not all, but those with an atomic number ≥76) over metal NPs is their tendency to provide additional properties, such as X-ray attenuation and near-infrared activity. The combination of these properties translates to noble MNPs for therapeutic and diagnostic applications, independent of the need for additional active molecules. Through this review, we highlighted the potential application of all noble MNPs and the limited use of osmium, iridium, palladium, rhodium, and ruthenium metal NSs, even though they express similar physicochemical characteristics. The literature search was limited by PubMed, full-text availability, and studies including both in vitro and in vivo models.